ANALISIS PELAKSANAAN FUNGSI BADAN PERMUSYAWARATAN DESA (BPD) DALAM PENYELENGGARAAN PEMERINTAHAN DESA DI DESA PENGALIHAN KECAMATAN KERITANG KABUPATEN INDRAGIRI HILIR - Irsal Mahendra, Yusril; Ramadhani Agusti Nst, Fitria (Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir Riau, 2025)
The Village Consultative Body (BPD) is a representative body consisting of community leaders in the village whose function is to establish village regulations together with the village head and to accommodate and channel community aspirations. The aim of the research is to determine the implementation of the functions of the BPD, in the administration of village government in the village of Keritang sub-district, Indragiri Hilir Regency, and to find out what are the obstacles to implementing the functions of the BPD in the administration of village government in the diversion of Keritang sub-district, Indragiri Hilir Regency. The techniques of this research are observation, interviews and documentation, based on research indicators, Discussing and agreeing on draft village regulations with the village head, accommodating and channeling the aspirations of the village community, monitoring the performance of the village head. The inhibiting factors are the lack of human resources, facilities and infrastructure, and lack of socialization. Badan Permusyawaratan Desa (BPD) adalah suatu badan perwakilan yang terdiri atas pemuka-pemuka masyarakat di Desa yang berfungsi menetapkan peraturan desa bersama kepala desa serta menampung dan menyalurkan aspirasi masyarakat,Tujuan Penelitian untuk mengetahui pelaksanaan fungsi BPD, dalam penyelenggaraan pemerintahan Desa di Desa Pengalihan Kecamatan Keritang Kabupaten Indragiri Hilir,dan untuk mengetahui apa kendala pelaksanaan fungsi BPD dalam penyelenggaraan pemerintahan desa di Pengalihan Kecamatan Keritang Kabupaten Indragiri Hilir,Teknik-teknik penelitian ini yaitu observasi,wawancara,dan dokumentasi,berdasarkan indicator penelitian ,Membahas dan menyepakati rancangan peraturan desa bersama kepala desa,menampung dan menyalurkan aspirasi masyarakat desa,melakukan pengawasan kinerja kepala desa.Faktor penghambatnya adalah kurangnya sumber daya manusia,sarana dan prasarana,dan kurangnya sosialisasi.